2020
DOI: 10.1142/s2737416521500022
|View full text |Cite
|
Sign up to set email alerts
|

An Ultimate Investigation on the Adsorption of Amantadine on Pristine and Decorated Fullerenes C59X (X=Si, Ge, B, Al, Ga, N, P, and As): A DFT, NBO, and QTAIM Study

Abstract: In this investigation, the feasibility of detecting the amantadine (AMD) molecule onto the outer surface of pristine fullerene (C[Formula: see text]), as well as C[Formula: see text]X ([Formula: see text], Ge, B, Al, Ga, N, P, and As) decorated structures, was carefully evaluated. For achieving this goal, a density functional theory level of study using the HSEH1PBE functional together with a 6-311G(d) basis set has been used. Subsequently, the B3LYP-D3, wB97XD and M062X functionals with a 6-311G(d) basis set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

6
4

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…This, in turn, motivates the development and exploitation of selective sensors that can efficiently detect potential emissions of HCFC-124 in the atmospheric environment. For instance, a wide range of nanomaterials have been developed and tested for gas sensors that can have low limits of detection, high measurement accuracy, low response time, resistant to variable environmental conditions, as well as low production cost [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, motivates the development and exploitation of selective sensors that can efficiently detect potential emissions of HCFC-124 in the atmospheric environment. For instance, a wide range of nanomaterials have been developed and tested for gas sensors that can have low limits of detection, high measurement accuracy, low response time, resistant to variable environmental conditions, as well as low production cost [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, theoretical studies on nanoscale structures have found an extraordinary place in computational chemistry, and researchers have used numerous computational methods to study intermolecular interactions to design tools that have better accuracy and performance [1][2][3][4][5]. A variety of nanomaterials have been considered for the construction of sensors with high measurement accuracy, extreme insensitivity to temperature, very low response time, low production costs, and resistant to harsh environmental conditions [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the optoelectrical, mechanical, and thermal properties [25] of such structures are still under consideration [26,27]. Furthermore, these nanomaterials are widely used, for example, as nanocarrier [28][29][30][31][32][33][34][35][36][37][38][39] or nanocarriers of drugs [40][41][42]. These processes occur through adsorption (adhesion of a particle to a surface), and they are primarily related to the intermolecular interactions between the adsorbent and the adsorbate.…”
Section: Introductionmentioning
confidence: 99%